Rancang Bangun Robot Tempur Menggunakan Mikrokontroller Ultrasonic Dan Warna - Rofiq, Mochammad Dimas Ainur; Dirgantoro, Guruh Putro; Roihatur Rohmah, Roihatur Rohmah (Multidisciplinary Applications of Quantum Information Science (Al-Mantiq), 2025)
Design and Development of Combat Robots Using Ultrasonic and Color Microcontrollers. Thesis, Computer Systems Study Program. Faculty of Science and Technology. Nahdlatul Ulama Sunan Giri University. Main Supervisor Guruh Putro Dirgantoro, M.Kom and Assistant Supervisor Roihatur Rohmah M.Si. Technology is an important aspect for humans that influences the progress of a nation in competing to make cards of various types, such as making combat robots (battelbots) based on Arduino Uno and Arduino nano microcontrollers equipped with distance sensor modules, colors, LCD modules as displays. enemy value and the motor driver module as the driving force for the robot, by using R&D Research and Development to collect data and analyze and using the Arduino IDE application to create coding for the combat robot project, the design and construction of this project can run well as expected, with the existence of error When experiencing gaps in the socket, the implication of this research is the development of Arduino Uno and Nano devices with distance sensor modules, color and LCD modules, motor drivers as the way for this fighting robot. This robot can be a solution in implementing or developing Arduino extracurriculars and organizing combat robot events among young people. In conclusion, Arduino Uno and Arduino nano can be applied to combat robots equipped with distance, color, LCD and motor driver sensor modules. This research is proof that it provides good value to young people in the learning process based on remote or automatic combat robots that use Arduino.